Analisis Metakognitif Siswa dalam Menyelesaikan Soal Asesmen Kompetensi Minimum ditinjau dari Kecerdasan Emosional dan Gaya Belajar Siswa - Hamda, Hamda; Ahmad , Andi Elsah Nur Azizah A.; Ja’faruddin, Ja’faruddin (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2024)
This study aims to describe students' metacognitive abilities in solving Minimum Competency Assessment (AKM) questions in terms of emotional intelligence and learning styles. This research is a descriptive research with a qualitative approach. The research instruments used were tests in the form of AKM questions and interviews. The selection of subjects is based on the categorization level of the results of the emotional intelligence questionnaire and learning style. The results showed that students who have high emotional intelligence with visual, auditory, and kinesthetic learning styles, are able to plan, monitor, and evaluate the results of their work properly and accurately. However, students with high emotional intelligence with visual and kinesthetic learning styles are more able to express and explain the results of their thoughts clearly and coherently. Meanwhile, students who have low emotional intelligence with visual, auditory, and kinesthetic learning styles have not been able to plan, monitor, and evaluate their work properly. These students tend not to be able to understand the problem information and have not been able to plan the solution steps appropriately. In this study it was also found that students who have visual, auditory, and kinesthetic learning styles do not have differences in the quality of the three styles or vice versa. Each student has their own characteristics in solving the problems given. This is largely influenced by the emotional intelligence possessed by students.